2020
DOI: 10.3390/ijgi9110686
|View full text |Cite
|
Sign up to set email alerts
|

Density-Based Spatial Clustering and Ordering Points Approach for Characterizations of Tourist Behaviour

Abstract: Knowledge about the spots where tourist activity is undertaken, including which segments from the tourist market visit them, is valuable information for tourist service managers. Nowadays, crowdsourced smartphones applications are used as part of tourist surveys looking for knowledge about the tourist in all phases of their journey. However, the representativeness of this type of source, or how to validate the outcomes, are part of the issues that still need to be solved. In this research, a method to discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Tourist flow can depict the spatial distribution of tourists from a dynamic perspective. Scholars usually use Markov chains [13], spatial clustering [14], kernel density estimation [15], exploratory spatial data analysis [16], and other methods to detect the spatial patterns of tourist flows. In recent years, the introduction of network science has provided a new way to analyze tourist flow [17].…”
Section: Introductionmentioning
confidence: 99%
“…Tourist flow can depict the spatial distribution of tourists from a dynamic perspective. Scholars usually use Markov chains [13], spatial clustering [14], kernel density estimation [15], exploratory spatial data analysis [16], and other methods to detect the spatial patterns of tourist flows. In recent years, the introduction of network science has provided a new way to analyze tourist flow [17].…”
Section: Introductionmentioning
confidence: 99%
“…The researchers in [13] used spatial clustering methods to mine tourist destinations and preferences, in which the regions of tourist attractions for each tourism category were derived by the clustering algorithm. The researchers in [14] used a density-based spatial clustering algorithm to study tourist behavior, and by extracting the tourist behaviors, the tourism hot-spots were extracted as they related to tourist behavior. In [15], the clustering algorithm was used to generate tourist-attraction clusters via network and geographic information system (GIS) analyses, and three tourist-attraction clusters were extracted.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in [1][2][3][4][5][6][7], clustering algorithms have been used in tourism research for POI extraction, data mining, algorithm modeling, transportation behavior, etc. The other clustering methods in [8][9][10][11][12][13][14][15] indicated that spatial and attribute data of tourist attractions were the main targets that were used to generate proper tourism categories, extract tourist preferences, and recommend appropriate tourist destinations. The studies concerning tourist-attraction data extraction and tour-route algorithms that were used in [16][17][18][19][20][21][22][23][24][25][26][27][28][29] focused on three specific aspects.…”
Section: Introductionmentioning
confidence: 99%
“…As already mentioned, accessibility has great impact on a key economic driving sector such as tourism [8]. Many scientific studies focus on tourist trends, proposing theories about their behavior to predict even their seasonality [9,10]. Within the different typologies of tourism, the following research refers to cultural tourism, studying behavior through images of geolocation techniques to even propose tourist routes within the different cities [11].…”
Section: Introductionmentioning
confidence: 99%